Effects of vocabulary on acquaring basic language skills and academic disciplines - Yalçin, Süleyman Kaan; Özek, Fatih (My University, 2006)
People communicate with each other and outside world by means of words that provide the outside world's being perceived, made meaningful and transferred and basic language skills consisting of the activities like listening, speaking, reading and writing which are shoped by these words, with this side of them, people owe their all ideal and comunicative activites in their life environment to the words that make the outside world be symbolized by being dissociated. Because vocabulary, which means the whole words and structures formed by these words, is an important factor while making the people get the ability to perceive, form thougts, understand, make meaningful, comment on and transfer. In this study, the relationship of the academic disciplines that shope the life environment of people and which are developed in the direction of the basic language skills with vocabulary is discussed.
Söz varli?inin temel di?l beceri?leri?ni?n ve akade?ik di?si?pli?nleri?n kazanimina olan etk?ile?i
Keywords: Basic language skills and academic disciplines; Language; Language - Thought relationship; Vocabulary; Word